FAKTOR YANG MEMPENGARUHI PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS MALINAU TAHUN 2025 - Jumiyatie, Rahmatul; Rusmilawaty, Rusmilawaty; Laili , Fitria Jannatul; Yuliastuti, Erni (Seroja Husada: Jurnal Kesehatan Masyarakat, 2025)
Background: Exclusive breastfeeding is essential for infant growth and health. However, its coverage in the working area of Malinau Primary Health Centre remains low 52,3%. The coverage has not reached the national target of 80%. This study aimed to identify factors influencing exclusive breastfeeding practices. Methods: This quantitative research employed a cross-sectional design. Ninety-two breastfeeding mothers with infants aged >6-24 months were selected using purposive sampling. Data were collected through structured questionnaires and analyzed using the Chi-Square test. Results: Univariate analysis showed that most respondents were aged 20–35 years (51.1%), had primary education (67.4%), were unemployed (66.3%), were multiparous (56.5%), had poor knowledge (57.7%), and received supportive family support (71.7%). A total of 52.2% of respondents did not practice exclusive breastfeeding. Bivariate analysis revealed significant associations between exclusive breastfeeding and maternal age (p=0.002), occupation (p=0.022), knowledge (p=0.042), and family support (p=0.012). In contrast, education level (p=0.959) and parity (p=0.067) showed no significant association.